Perceived Sources of Stress among Junior & Mid-Senior Egyptian Dental Students - Abdel Karim, Nabila Ahmed Sedky (International Journal of Health Sciences, 2012)
Objectives: The purpose of this study was to identify the sources of stress among dental students enrolled at Pharos University in Alexandria (PUA) - Egypt, and to explore the role of gender, level of undergraduate study and residence with parents on perceived stressors. Materials and Methods: A thirty-item self-reported modified version of the Dental Environment Stress (DES) questionnaire was adminÂistered to 537 junior and mid-senior undergraduate dental students during the academic fall semester 2010, with a response rate of 79.89%. Results: Workload, performance pressure, and self-efficacy beliefs constituted the most stress-provoking factors. Female students experienced greater stress than males for all stressor items except for â€œSelf-Efficacy Beliefsâ€ and â€œFaculty & Administrationâ€ with no statistically significant difference by gender. Mid-senior dental students registered higher levels of perceived stress for â€œWorkloadâ€, â€œSelf-Efficacy Beliefsâ€, and â€œPersonal Factorsâ€ stressors in comparison to their junior peers. Those students who lived away of their parents were at higher risk of perceived stress than those students who lived with their parents. â€œUncertainty about future dental careerâ€ was the first best predictor variable by gender. Whereas, â€œDifficulty of classworkâ€ was the first predictor variable by both level of undergraduate study and residence with parents. Conclusion: Female dental students had higher mean overall problem scores compared to their male counterparts, mid-senior students showed some higher perceived problems compared to junior students, and students who lived away from their parents revealed higher levels of perceived stress. Key words: dental students, perceived stress, gender, level of undergraduate study, residence with parents.